The Development of a Digital Marketing System to Improve Marketing and Sales of MSME Products in Kepudibener Village through Social Media - Titik Khotiah; Evi Dwi Kartikasari; Muhammad Nurul Huda; Abdul Rohman (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
. Digital marketing aims to attract consumers and potential consumers quickly. The acceptance of technology and the internet in society is very broad, so it is not surprising that digital marketing activities are the main choice by companies. Companies compete with each other to create interesting content to be displayed in their marketing in cyberspace. The approach in this research is the Participatory Rural Appraisal (PRA) method. In the digital marketing development activities in Kepudibener Village, the team from KKN 2 ITB Ahmad Dahlan Lamongan hopes that the training and mentoring related to digital marketing can encourage the enthusiasm of MSME players to utilize digital media in increasing sales and marketing of products owned by each MSME in Kepudibener Village, and can expand sales networks and relationships because in product sales relationships are very important to encourage MSMEs to develop faster in offline and online markets.